Effect of benzylaminopurine (BAP) on in vitro proliferation and growth of pineapple (Ananas comosus L. Merr.) cv. smooth cayenne - Hamad, A.M.; Taha, R.M. (2008)
The effect of 6-benzylaminopurine (BAP) at concentration range of 0 to 3.75 mg L-1 applied at concentration difference of a fixed increment of 0.25 mg L-1 on the in vitro shoot formation and average and total of shoot length and weight per explant of smooth cayenne pineapple were evaluated. BAP significantly affected the average of shoot number, length and weight but did not affect the total length and total weight per explant. The maximum shoot formation (12 shoots/explant) occurred at 4 concentrations of BAP (1.75, 2.0, 2.25 and 3.5 mg L-1) while tallest (25 mm) and heaviest (0.60 g) shoots obtained on MS hormone free medium. Shoot formation pattern showed two sudden increases in shoot formation. The first occurred at 1.25 and second at 3.50 mg L-1 and two sharp declines at 2.5 and 3.75 mg L-1. Identifying of the concentrations with contrasting effect where an increase and decline in the shoot formation pattern occur provide an essential base from which an informative successful histological and biochemical studies could be designed to elucidate shoot formation mechanism. Â© 2008 Asian Network for Scientific Information.